THE INDIVIDUALIZATION OF ERP IN SMES FOR SUSTAINABLE DEVELOPMENT - Shih, Wurong; Montes, Julián Nevárez (International Journal of Small and Medium Enterprises, 2022)
This paper aims to prove that software such as Enterprise Resource Planning (ERP) is not designed properly and is out of the awareness of most Small and Medium Enterprises (SMEs). The Expectation-Confirmation model took role as a way of understanding this behavior and the application of a questionnaire of validation in three specific areas: sales, inventory management and customer satisfaction to 47 hair salons in Bolivia, Chile, China, Colombia, Ecuador, Mexico, Peru, The U.S. and Taiwan. A concise finding is that in fact, managers, owners and employees in hair salons are not aware of the existence of ERP solutions and the possible application to their business so that their sustainable development is achieved; also, the main finding is that 87% are willing to learn and acquire it.JEL Classification Codes: A19, B10, B25, C10, C53.